EVALUASI PENENTUAN KOS PRODUK DENGAN METODE JOB COSTING PADA PERUSAHAAN MAHKOTA MULYO MANDIRI SKRIPSI - , LUCY MARTHIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mahkota Mulyo Mandiri is a medium manufacturing company, specialized in furniture production for Indonesian consumption as well as for worldwide exports. It is located in industrial district of Jepara, Indonesia. Most of its products are tailor-made. As a medium enterprise, Mahkota Mulyo Mandiri found it difficult to accurately assess the product cost of each product with its traditional method. The company also has an inappropriate cost flow and manufacturing costs classification. The inappropriate product cost will lead to inappropriate selling price and hinder the profit maximization. The case-study research aims at determining product cost accurately. To achieve the objective, the researcher proposes implementing job-costing method to simplify the methodology for calculating product cost accordance with the objective. This method will help to trace the direct cost and allocate the indirect cost appropriately based on the 7 steps in job-costing. The case study begins with cost flow and manufacturing cost classification correction. Fourteen samples were chosen to find out the accuracy of job-costing method compared with traditional method. The mathematical analysis result shows that the job-costing method provides higher product cost than the traditional method does because of the inclusion of the overhead cost. Even though job-costing method causes a higher product cost, it is more accurate and reliable to be applied for the company with distinctive products. The research result reveals that the job-costing method has full applicability in this case, and in conclusion, it has a real value in product cost determination. The method helps the owner to define an accurate selling price, to manage the production costs, and to control the costs as well. Since Mahkota Mulyo Mandiriâs products are customized, there are no market prices for its products. To calculate the selling price, Mahkota Mulyo Mandiri might apply cost-plus pricing method that is really simple and helpful for the company to define the expected profit more easily.